Habitat Alami Brugia Malayi Nonperiodik Penyebab Filariasis Di Kalimantan Timur - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT A non periodic form of Brugia malayi Lichtenstein was previously reported from East Kalimantan as a new Brugia type/subspecies of human parasite filarial worm'. 2.3. This paper reports the type of environment of deep forest (forest-swamp) in Krayan area, Long lkis district, the regency of Pasir, which becomes the natural habitat of the B. malayi type. The results of blood and clinical examinations carried out on indigenous inhabitants (Dayak people) in the forest area reveals that the disease transmission occurred efficiently (filariasis rate 47.6 %, microfilarial rate 34.0 %, clinical rate 29.7 %, elefantiasis rate 2.3 %).